Post-Operative Glucose and HbA1c Levels in Patients Diagnosed with Cataract - Nurmeily Rachmawati; Srimaya Winahyu; Ahmad Yani; Venny Patricia (Journal of Noncommunicable Diseases Prevention and Control, 2024)
Diabetes mellitus is known as a disease that continues to increase every year in the world. This disease can cause severe complications in several organs, including the heart, nerves, kidneys, eyes, and skin. One of the problems that arise in diabetes patients with complications in the eye area is cataracts. Cataract patients are generally treated by operating on the eye through light surgery. One way to evaluate the health status of postoperative cataract patients is by observing laboratory examination results, especially blood glucose and HbA1c parameters. This study aimed to determine the description of glucose and HbA1c levels in patients after cataract surgery. Respondents totaled 30 patients, with 17 and 13 women and men, respectively. The method used in this research is descriptive analysis with laboratory examination as the primary data source. Based on the results, most respondents were 60 years and under (60%). The results showed that 33.3% of respondents' postoperative glucose levels were above the normal limit (>150 mg/dL). Meanwhile, as many as 30% of respondents' postoperative HbA1c levels were above the normal limit (>6.5%). Based on gender, postoperative glucose and HbA1c levels, which are above normal, are dominated by men. Meanwhile, based on age, postoperative glucose and HbA1c levels above normal were dominated by the age group ≤60 years.